Three-dimensional BiOI/BiOX (X = Cl or Br) nanohybrids for enhanced visible-light photocatalytic activity - Liu, Y.; Xu, J.; Wang, L.; Zhang, H.; Xu, P.; Duan, Xiaoguang; Sun, H.; Wang, Shaobin (2017)
© 2017 by the authors. Licensee MDPI, Basel, Switzerland.Three-dimensional flower-like BiOI/BiOX (X = Br or Cl) hybrids were synthesized via a facile one-pot solvothermal approach. With systematic characterizations by X-ray diffraction (XRD), scanning electron microscopy (SEM), Transmission electron microscopy (TEM), the Brunauer-Emmett-Teller (BET)specific surface area, X-ray photoelectron spectroscopy (XPS), and the UV-Vis diffuse reflectance spectra (DRS), the BiOI/BiOCl composites showed a fluffy and porous 3-D architecture with a large specific surface area (SSA) and high capability for light absorption. Among all the BiOX (X = Cl, Br, I) and BiOI/BiOX (X = Cl or Br) composites, BiOI/BiOCl stands out as the most efficient photocatalyst under both visible and UV light irradiations for methyl orange (MO) oxidation. The reaction rate of MO degradation on BiOI/BiOCl was 2.1 times higher than that on pure BiOI under visible light. Moreover, BiOI/BiOCl exhibited enhanced water oxidation efficiency for O2 evolution which was 1.5 times higher than BiOI. The enhancement of photocatalytic activity could be attributed to the formation of a heterojunction between BiOI and BiOCl, with a nanoporous structure, a larger SSA, and a stronger light absorbance capacity especially in the visible-light region. The in situ electron paramagnetic resonance (EPR) revealed that BiOI/BiOCl composites could effectively evolve superoxide radicals and hydroxyl radicals for photodegradation, and the superoxide radicals are the dominant reactive species. The superb photocatalytic activity of BiOI/BiOCl could be utilized for the degradation of various industrial dyes under natural sunlight irradiation which is of high significance for the remediation of industrial wastewater in the future.